Manufacturing method for insulating circuit board
By controlling the vacuum level in the bonding process of ceramic substrates and copper plates, the method enhances bonding reliability in power modules, addressing the issue of vacuum degradation and repeated thermal cycling.
Patent Information
- Application Number
- JP2021060361
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-03-31
AI Technical Summary
Existing methods for bonding ceramic substrates to copper plates in power modules suffer from poor bonding reliability when subjected to repeated cold-heat cycles due to vacuum degradation during the bonding process.
The method involves controlling the vacuum level in the heating furnace to below 1.0×10^-2 Pa within a temperature range of 600°C to 770°C, and maintaining this level by suppressing gas generation through pre-heating of the pressurizing jig and using metal insulation in the heating furnace.
This approach significantly improves bonding reliability by reducing vacuum degradation, ensuring stable bonding not only initially but also under repeated cooling and heating cycles.
Smart Images

Figure 0007655046000002 
Figure 0007655046000003 
Figure 0007655046000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an insulating circuit board used in a power module or the like for controlling a large current and a high voltage. [Background technology]
[0002] Conventional insulating circuit boards used in power modules and the like are made of, for example, AlN (aluminum nitride), Al 2 O 3 (Alumina), Si 3 N 4 The ceramic substrate is provided with a ceramic substrate made of silicon nitride or the like, a circuit layer formed on one side of the ceramic substrate, and a heat dissipation layer formed on the other side of the ceramic substrate. A brazing material is generally used to bond the ceramic substrate to a metal plate that serves as the circuit layer or the heat dissipation layer. When the metal plate is a copper or copper alloy plate, a brazing material containing an active metal is used.
[0003] Patent Document 1 discloses a power module substrate in which a copper plate made of copper or a copper alloy is laminated and bonded to the surface of a ceramic substrate, in which a nitride layer is formed on the surface of the ceramic substrate between the copper plate and the ceramic substrate, and the Ag-Cu eutectic structure layer has a thickness of 15 μm or less. In this case, the ceramic substrate and the copper plate are pressurized in the lamination direction (pressure 1 to 35 kgf / cm) with an Ag and nitride-forming element layer interposed between them. 2 The materials are then heated in a vacuum heating furnace and joined together. The pressure in the vacuum heating furnace is 10 -6 Pa or more 10 -3 It is described that the pressure should be set within a range of 790° C. or more and 850° C. or less. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-179263 A Summary of the Invention [Problem to be solved by the invention]
[0005] As disclosed in Patent Document 1, in the past, the degree of vacuum achieved in the heating furnace during bonding was confirmed using the vacuum level attached to the heating furnace, etc. This bonding method does not impair bondability initially, but when a thermal cycle load is applied in which a cooling environment and a heating environment are repeatedly switched between, a problem occurs in which the bonding reliability deteriorates.
[0006] The present invention has been made in view of the above circumstances, and has an object to reconsider the bonding conditions and obtain good bonding reliability even in an environment where cooling and heating are repeated. [Means for solving the problem]
[0007] The method for producing an insulating circuit board of the present invention is a method for producing an insulating circuit board having a copper layer on a surface of a ceramic substrate by laminating a ceramic substrate and a copper plate made of copper or a copper alloy with a brazing material interposed therebetween, and heating the ceramic substrate and the copper plate in a heating furnace while applying pressure in the lamination direction to bond the ceramic substrate and the copper plate, the method comprising the steps of: maintaining a degree of vacuum in the heating furnace at a temperature range of 600° C. to 770° C. to 1.0×10 -2 Pa or less.
[0008] Since the bonding is performed between a ceramic substrate and a copper plate, the bonding temperature is 790°C to 850°C, as described in Patent Document 1, and the degree of vacuum at that time is 10 -6 Pa or more 10 -3The bonding temperature is set to a range of 100 Pa or less, but the degree of vacuum may decrease before reaching the maximum bonding temperature and maximum degree of vacuum, and the desired degree of vacuum may not be obtained. It is assumed that the decrease in degree of vacuum (vacuum deterioration) is the cause of the deterioration of bonding reliability in an environment where cooling and heating are repeated. In other words, gas is generated in the heating furnace in a specific temperature range before reaching the maximum bonding temperature, and vacuum deterioration occurs due to the influence of the gas. The inventor of the present invention made the above-mentioned invention based on the recognition that bonding reliability can be improved by suppressing this vacuum deterioration.
[0009] That is, the present invention controls the maximum bonding temperature and maximum degree of vacuum while suppressing gas generation, and the degree of vacuum during the temperature rise process, specifically, the degree of vacuum in the temperature range of 600°C to 770°C, is 1.0 x 10 -2 Even if a small amount of gas is generated in the heating furnace in this temperature range, the degree of vacuum is controlled to be 1.0×10 -2 By ensuring a bonding strength of 0.1 Pa or less, the bonding reliability can be improved.
[0010] In this method for producing an insulating circuit board, the H 2 ,CO,CO 2 The ratio of each ion intensity is H 2 is 20.3% or less, CO is 50.9% or less, CO 2 It is preferable that the content of the saturation current is 4.0% or less.
[0011] If these gases are generated in excess of a certain amount, they will cause vacuum degradation. 2 and CO reduce the oxide film on the copper surface, and H generated by the reduction 2 O causes problems such as oxidizing the components of the joining material. It also penetrates into the molten joining material and causes voids. Therefore, by controlling the concentration of these gases to a specified value or less, the effects of the gas can be suppressed and the joining reliability can be improved. Effect of the Invention
[0012] According to the present invention, by controlling the degree of vacuum in a predetermined temperature range during bonding, good bonding reliability can be obtained even in an environment where cooling and heating are repeated. [Brief description of the drawings]
[0013] [Figure 1] 1 is a cross-sectional view showing an example of an insulating circuit board manufactured by the manufacturing method of the present invention. [Diagram 2] 2 is a cross-sectional view showing a layer structure of a laminate before bonding to the insulating circuit board in FIG. 1. [Diagram 3] 3 is a front view showing a pressing jig for pressing the laminate of FIG. 2. [Figure 4] FIG. 4 is a cross-sectional view showing a backing plate used in the pressing jig. [Diagram 5] FIG. 1 is a schematic diagram of a test apparatus. [Figure 6] 1 is a graph showing the relationship between temperature, ion intensity, and vacuum degree during a bonding process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the method for producing an insulating circuit board of the present invention will be described. The insulating circuit board manufactured by the manufacturing method of this embodiment is, for example, a power module substrate used in a power supply circuit. As shown in Fig. 1, this power module substrate 10 has a ceramic substrate 11, a circuit layer 12 formed on one surface of the ceramic substrate 11, and a heat dissipation layer 13 formed on the other surface of the ceramic substrate 11.
[0015] The ceramic substrate 11 prevents electrical connection between the circuit layer 12 and the heat dissipation layer 13. The ceramic substrate 11 is made of aluminum nitride (AlN), silicon nitride (Si 3 N 4 ), aluminum oxide (Al 2 O 3 Among them, silicon nitride is preferable because of its high strength. The thickness of the ceramic substrate 11 is set within the range of 0.2 mm to 1.5 mm.
[0016] The circuit layer 12 is made of copper or a copper alloy, which has excellent electrical properties. The heat dissipation layer 13 is also made of copper or a copper alloy. The circuit layer 12 and the heat dissipation layer 13 are formed, for example, by brazing a copper plate made of oxygen-free copper with a purity of 99.96 mass% or more to the ceramic substrate 11 with an active metal brazing material. The thickness of the circuit layer 12 and the heat dissipation layer 13 is set within the range of 0.1 mm to 5 mm.
[0017] 2, the power module substrate 10 configured in this manner is formed by laminating copper plates 12', 13' on both sides of a ceramic substrate 11 via a brazing material 21. A brazing material made of Ag-Ti or Ag-Cu-Ti is used as the brazing material 21. The brazing material 21 may be supplied in the form of a foil, or may be formed by applying a brazing material paste to the ceramic substrate 11 by screen printing or the like.
[0018] The laminate S of the ceramic substrate 11 and the copper plates 12', 13' laminated with the brazing material 21 interposed therebetween is placed in a heating furnace under pressure, heated to the joining temperature in a vacuum atmosphere, and then cooled to form a circuit layer 12 on one side of the ceramic substrate 11 and a heat dissipation layer 13 on the other side. In this case, the pressing tool used is, for example, that shown in FIG. This pressure application tool 110 comprises a base plate 111, a number of guide posts 112 attached vertically to the four corners of the upper surface of the base plate 111, a fixed plate 113 fixed to the upper ends of the guide posts 112, a pressure plate 114 supported by the guide posts 112 so as to be freely movable up and down between the base plate 111 and the fixed plate 113, and a biasing member 115 such as a spring provided between the fixed plate 113 and the pressure plate 114 to bias the pressure plate 114 downward.
[0019] The base plate 111, the fixed plate 113, the pressure plate 114, the guide post 112, etc. are made of a carbon composite material that is compounded with carbon fiber. The fixed plate 113 and the pressure plate 114 are arranged parallel to the base plate 111, and the laminate S is disposed between the base plate 111 and the pressure plate 114. In this case, a backing plate 30 is disposed on the side of the base plate 111 and the pressing plate 114 that contacts the laminate S to ensure uniform pressure.
[0020] As shown in FIG. 4, the backing plate 30 has a structure in which a graphite sheet 32 is sandwiched between two carbon sheets 31. The carbon sheet 31 is made of a heat-resistant hard carbon material in the shape of a flat plate and is sintered at a high temperature of about 3000° C. The carbon sheet 31 has a bulk density of 1.6 Mg / m 3 More than 1.9Mg / m 3 Below (1600kg / m 3 More than 1900kg / m 3 For example, G-347 (thermal conductivity: 116 W / mK, elastic modulus: 10.8 GPa) manufactured by Asahi Graphite Co., Ltd. can be used.
[0021] On the other hand, the graphite sheet 32 is made of a soft graphite material having cushioning properties, and is constructed by laminating multiple thin flake graphite films like mica, and is made by treating natural graphite with acid, forming it into a sheet, and rolling it. The graphite sheet 32 has a bulk density of 0.5 Mg / m 3 More than 1.3Mg / m 3 For example, Asahi Graphite Co., Ltd.'s T-5 (thermal conductivity: 75.4 W / mK, elastic modulus: 11.4 GPa) and Toyo Tanso Co., Ltd.'s graphite sheet PF (compressibility 47%, recovery rate 14%) can be used. When the backing plates 30 are disposed on both end surfaces of the laminate S, the carbon sheets 31 come into contact with both end surfaces of the laminate S.
[0022] Then, with the backing plates 30 placed on both end surfaces of the laminate S, pressure is applied in the lamination direction using a pressure jig 110, and the entire laminate S including the pressure jig 110 is heated in a vacuum atmosphere. The joining conditions are, for example, pressing the laminate S with a pressure of 0.1 MPa to 3.5 MPa, -6 Pa or more 10 -3 Heating is performed in a vacuum atmosphere of 1 Pa or less at a maximum bonding temperature of, for example, 790° C. or more and 850° C. or less for 1 to 60 minutes.
[0023] During this heat treatment, the solder material 21 is desolvated during the process of increasing the temperature inside the heating furnace. The degree of vacuum inside the heating furnace in the temperature range of 600° C. to 770° C. is set to 1.0×10 -2 It is important to keep the pressure below Pa. During the time it takes for the maximum bonding temperature and maximum vacuum to be reached, H is released from the internal structure, such as the carbon of the pressure jig 110, into the heating furnace. 2 , CO, CO 2 The generation of these gases can cause vacuum deterioration and may prevent the desired degree of vacuum from being obtained. Therefore, in the temperature range of 600°C to 770°C, the degree of vacuum in the heating furnace is set to 1.0 x 10 -2 By keeping the pressure below 1 Pa, the effect of generated gas is reduced.
[0024] For example, a copper oxide film is generally formed on the surfaces of the copper plates 12' and 13'. 2 In the presence of CO, the oxide film is reduced, resulting in H 2 O is generated, which makes the silver, titanium, and other elements contained in the copper and brazing material 21 easily oxidized. Titanium is particularly susceptible to oxidation, and H generated by the reduction of the copper oxide film 2 When oxidized by O, the oxidized titanium is adsorbed to the carbon originating from the dispersant around the silver in the brazing material 21. 3 N 4 The amount of titanium that contributes to the bonding of 11 is reduced, and the formation of titanium nitride is inhibited. 2 , CO, CO 2If the generation of gases such as these increases, bubbles may accumulate in the brazing material layer, and may not escape completely even when the material becomes molten, resulting in voids that remain. The combined effect of these factors reduces the reliability of the joint.
[0025] In this embodiment, the degree of vacuum in the heating furnace in the temperature range of 600° C. to 770° C. is set to 1.0×10 -2 In order to reliably control the pressure to below 10 Pa, for example, the carbon used in the pressurizing jig 110 is heated to a high temperature before use to release gas from the carbon in advance. Specifically, the pressurizing jig 110 is heated to, for example, 770°C (this is called air-baking). This causes gas components to be released from the pressurizing jig 110. In this case, all of the members of the pressurizing jig 110 are air-baked. Furthermore, if the pressurizing jig 110 is placed in a heating furnace and air-baked, the structures inside the heating furnace (for example, carbon insulation) are also air-baked and release gas.
[0026] Then, for actual bonding, the laminate S is pressurized and heated using the pressurizing jig 110 and heating furnace that have been subjected to the pre-baking. As a result, the gas is released in advance, so there is less influence from the gas during heating, and the degree of vacuum is 1.0×10 in the temperature range of 600°C to 770°C. -2 Even if a small amount of gas is generated, the effect of the gas can be reduced and the degree of vacuum can be reduced to 1.0×10 Pa or less. -2 It is possible to maintain the vacuum level at or below 550 Pa. It is even better to maintain the vacuum level at a temperature range of 550°C to 700°C.
[0027] In this way, while controlling the degree of vacuum in the temperature range of 600°C to 770°C, the bonding temperature is increased to 790°C to 850°C, and the degree of vacuum at the maximum temperature is maintained at 10 -6 Pa or more 10 -3 The bonding temperature and degree of vacuum are kept at 1 to 60 minutes, and then the bonding is cooled, whereby copper plates 12', 13' are bonded to ceramic substrate 12, and insulating circuit substrate 10 is formed in which copper layers (circuit layer 12, heat dissipation layer 13) are formed on both sides of ceramic substrate 11. This insulating circuit board 10 has a reduced effect of gas during the bonding process, and therefore has high bonding reliability, and can maintain stable bonding not only at the initial stage of bonding but also over the long term. The pressing jig 110 can be used multiple times, but it is advisable to carry out a baking step before each use.
[0028] The present invention is not limited to the configuration of the above embodiment, and various changes can be made to the details of the configuration without departing from the spirit of the present invention. In addition to the heating of the pressurizing jig 110 in the furnace, it is also effective to limit the use of carbon parts in the furnace. For example, the number of carbon parts in the furnace can be reduced by changing the heat insulating material in the furnace to a metal one. Furthermore, in the embodiment, the power module substrate 10 has been described as an insulating circuit substrate, but the present invention is also applicable to insulating circuit substrates other than power module substrates. EXAMPLES
[0029] S 3 N 4 A copper plate (37 mm x 37 mm x 0.3 mm) made of oxygen-free copper (OFC) with a purity of 99.99% by mass or more was laminated on one side of a ceramic substrate (40 mm x 40 mm x 0.32 mm) made of 100% by mass of Ag-8.8% by mass of Ti through a brazing paste. The laminate was pressed with a pressure of 1.5 MPa using the pressing tool described in the embodiment, and the laminate was heated to 1000° C. -5 The insulating circuit board was fabricated by heating to a bonding temperature of about 825°C for 30 minutes in a vacuum atmosphere of 0.1 Pa or less, and then cooling. Two types of insulating materials were prepared for the inside of the heating furnace: metal and carbon. The carbon insulating materials were used in two types: one that had been pre-heated and one that had not been pre-heated. Two types of pressure jigs were also used: one that had been pre-heated and one that had not been pre-heated.
[0030] In addition, the maximum degree of vacuum in the temperature range of 600° C. to 770° C., the maximum bonding temperature, and the degree of vacuum at that temperature were each measured. In addition, in the temperature range of 600°C to 770°C, H in the heating furnace 2 concentration, CO concentration, CO 2 The concentration was measured. For the measurement, as shown in the test equipment in FIG. 5, a quadrupole mass spectrometer 53 (Qulee with YTP model BGM-202) manufactured by ULVAC, Inc. was connected to a port 52 of a heating furnace 51, and the gas components in the heating furnace 51 were analyzed while the port 52 was evacuated with a turbo molecular pump 54. The degree of vacuum was measured with a Penning gauge 55 (CT-3DA manufactured by Daia Vacuum Co., Ltd.) connected to the port 52. In this case, an oil diffusion pump 57 was provided on a vacuum piping 56 in the heating furnace 51, and the port 52 for gas analysis was installed on the opposite side of the oil diffusion pump 57.
[0031] The ion intensity was measured every 10 seconds by the quadrupole mass spectrometer 53, and the ion intensity ratio of the gas components in the heating furnace 51 was calculated. 2 ,CO,CO 2 The ratio of the ion intensities was calculated as the ratio of the ion intensities (individual ion intensity / total ion intensities with mass numbers of 2 to 200 x 100). The maximum values in the temperature range of 600°C to 770°C are shown in Table 1.
[0032] The bonded insulating circuit board was then subjected to a thermal cycle test at -40°C to 150°C for 2000 cycles. After the test, the bonding surface between the ceramic substrate and the copper layer of the insulating circuit board was subjected to ultrasonic testing. The ultrasonic testing image was then binarized to determine the bonded area excluding the peeled portion. The bonding rate was calculated by dividing this by the area of the interface to be bonded. The results are shown in Table 1.
[0033] [Table 1]
[0034] As shown in Table 1, during the heating process of the heating furnace, the temperature range of 600°C to 770°C was 1.0×10 -2In Examples 1 and 2, in which the degree of vacuum was controlled to 100 Pa or less, the decrease in the bonding rate was small not only immediately after bonding but also after a thermal cycle load, and excellent bonding reliability was maintained. In this case, it is found that it is effective to change the insulating material in the heating furnace to metal or to bake the carbon insulating material in the furnace while baking the pressure jig.
[0035] 6 is a graph showing the transition of the temperature and degree of vacuum in the heating furnace and the ion intensity of each gas component in Example 1, where the left vertical axis is the ion intensity (A), the right vertical axis is the degree of vacuum (Pa), and the horizontal axis is the temperature (°C). The transition of the pressure value of the Penning gauge is also shown. As can be seen from FIG. 6, the ionic strength of each gas component increases up to 770° C., and gas is released into the heating furnace 51. At that time, the degree of vacuum is 1.0×10 -2 Pa or less.
[0036] In contrast, vacuum deterioration is large in the temperature range between 600°C and 770°C, reaching 1.0×10 -2 Comparative Examples 1 and 2, which had a vacuum degree exceeding 100 Pa, had excellent bonding reliability at the initial stage of bonding, but the bonding rate decreased after the thermal cycle load, resulting in poor bonding reliability. In this case, even if the carbon insulating material in the heating furnace is pre-baked, if the pressure jig is used without pre-baking, the vacuum will deteriorate and the bonding reliability after the thermal cycle will deteriorate. [Explanation of symbols]
[0037] 10 Power module substrate (insulated circuit substrate) 11 Ceramic substrate 12 circuit layer (copper layer) 13 Heat dissipation layer (copper layer) 12´,13´ copper plate 21, 22 Brazing layer 30 Backing Plate 31 Carbon Sheet 32 Graphite Sheet 51 Heating Furnace 52 Port 53 Quadrupole mass spectrometer 54 Turbomolecular pump54 55 Penning Gauge 56 Vacuum piping 57 Oil diffusion pump 110 Pressurizing tool 111 Base plate 112 Guide Post 113 Fixed plate 114 Pressure plate 115 Pressing member
Claims
1. A method for manufacturing an insulated circuit board having a copper layer on a surface of a ceramic substrate, comprising: laminating a ceramic substrate and a copper plate made of copper or a copper alloy with a brazing material interposed therebetween; heating the ceramic substrate and the copper plate in a heating furnace while applying pressure in the lamination direction with a pressure jig, thereby bonding the ceramic substrate and the copper plate; and maintaining a degree of vacuum in the heating furnace in a temperature range of 600° C. to 770° C. to be 1.0×10 -2 and then heating to a maximum bonding temperature of 790° C. or more and 850° C. or less in a vacuum atmosphere of 10 −6 Pa or more and 10 −3 Pa or less.
2. In the above temperature range, the ratio of H to the total ion intensity of the mass number of 2 to 200 measured by a quadrupole mass spectrometer is 2 , CO, CO 2 The ratio of the ionic strength of each of H 2 is 20.3% or less, CO is 50.9% or less, CO 2 2. The method for producing an insulating circuit board according to claim 1, wherein the insulating circuit board has a surface roughness of 4.0% or less.
3. The method for manufacturing an insulated circuit board as described in claim 1, characterized in that the pressure jig contains carbon that has been heated in advance to release gas.
Citation Information
Patent Citations
Method for joining ceramic substrate with metal plate
JP1998158073A
Ceramic circuit board and method of manufacturing the same
JP2002171037A
Ceramic circuit board
JP2005252087A
Power module substrate, power module substrate with heat sink, power module, and method for manufacturing power module substrate
JP2013179263A
Nitride based ceramic circuit board
JP2014091673A